AKTIVITAS ANTIOKSIDATIF DAN HIPOKOLESTEROLEMIK EKSTRAK TEH HIJAU DAN TEH WANGI PADA TIKUS YANG DIBERI RANSUM KAYA ASAM LEMAK TIDAK JENUH GANDA [Antioxidative and Hipocholesterolemic Activity of Green Tea and Jasmine Green Tea Extracts in Rats Fed wi - Arif Hartoyo; Mary Astuti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
The aim of this study was to evaluate in-vivo the antioxidative and hipocholesterolemic activity of green tea and jasmine green tea extracts in 3.5-month-old Sprague Dawley male rats given high PUFA diet for 4 weeks. In rats fed with (adlibidom or forcely adted) high PUFA diet supplemented with green tea extract, serum and liver homogenate malondialdehyde level and the liver homogenate cholesterol level were greater than rats fed with the high PUFA diet supplemented with jasmine green tea extract pn the control. In contrast, no change was observed in serum cholesterol level in rats fed with the high PUFA diet containing green tea or jasmine green tea extract as compared with the high PUFA diet.